Killer in the kitchen : a Murder she wrote mystery - Bain, Donald, 1935-2017 (Fletcher, Jessica. Murder, she wrote, 2015)
"Jessica may not know everything about food, but she knows what she likes--and she definitely likes the Leg & Claw restaurant. Opened last summer by young couple Brad and Marcie, the Leg & Claw is their dream come true, combining Marcie's sunny personality with Brad's deft hand in the kitchen. But now their dream is turning into a nightmare. Gérard "Pepe" Leboeuf is a renowned New York City restaurateur who has a summer home in Cabot Cove. And now he's decided to open two new restaurants there--in an old warehouse right next to the Leg & Claw. As Leboeuf and his crew renovate the warehouse, the people of Cabot Cove slowly come to the realization that the town's newest celebrity may be more trouble than he's worth. His "assistants" are little more than thugs, and the haughty Leboeuf is nowhere near as charming as he seems--leading to a nasty confrontation with Brad. So when Leboeuf is found dead with a knife planted in his chest, Brad naturally becomes suspect number one. But plenty of others had a motive to kill Pepe, and it's up to Jessica to uncover who really added murder to the menu"--